Socialization Of Effective Learning And Savings From An Early Age To Elementary School Students - Ahyar, Juni; Ikramuddin, Ikramuddin; Zulkifli, Zulkifli (Devotion : Journal of Community Service, 2021)
First, the problem in Meunasah Teungoh Village, Simpang Keuramat District is about education, namely where the learning process in schools is still less effective and efficient. The teaching and learning process in two schools in Gampong Meunasah Teungoh, namely SD Negeri 5 Simpang Keuramat still tends to seem monotonous and boring. The children/students have not been able to catch what the teachers are saying, thus causing the process of delivering the material not to be well received by the children/students. This of course makes children's knowledge less and tends not to be able to apply it directly in society. Therefore, through the service in the form of effective learning socialization that we will do in the two schools, it makes the children/students more enthusiastic in learning and enthusiastic in receiving all the knowledge that we provide. Second, the problem in Gampong Meunasah Teungoh is the lack of awareness of children in cultivating saving from an early age. This is due to the lack of attention from parents and school institutions in providing knowledge and teaching about the importance of saving from an early age. Children tend to have a desire to spend the pocket money given by their parents quickly so that when an urgent situation comes, they have no savings. Therefore, we will conduct socialization activities on saving from an early age to children, by providing knowledge through games to them about the importance of saving from an early age.